2019
DOI: 10.18203/2320-1770.ijrcog20193106
|View full text |Cite
|
Sign up to set email alerts
|

Maternal outcome of primigravida patient with term pregnancy with engaged versus unengaged foetal head at onset of labour

Abstract: Background: The primigravida are a group at risk as their capacity of child bearing has never put to the test, “primigravida is a dark and untired horse". The potential for future child bearing is determined by outcome of first labour. Hence, if first pregnancy results in normal healthy child, patient is mentally better prepared for subsequent pregnancies. Foetal head is said to be engaged when its biparietal diameter, the greatest diameter in an occiput presentation, passes through the pelvic inlet. Unengagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
1
7
1
Order By: Relevance
“…Adita et al reported a comparative study of 110 women with unengaged head (group A) and 110 women with engaged head (group B). 4 There were 15 cases in group A and 9 cases in group B with age more than 30 years. In the present study there was only 1 case each in both groups.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Adita et al reported a comparative study of 110 women with unengaged head (group A) and 110 women with engaged head (group B). 4 There were 15 cases in group A and 9 cases in group B with age more than 30 years. In the present study there was only 1 case each in both groups.…”
Section: Discussionmentioning
confidence: 91%
“…According to Aditi et al and Mahendra et al non progress of labour was common indication in group A. 1,4,6 According to Siama et al total duration of labour in 34% of group A and 74% of group B was<12 hours. 6 Remaining 66% in group A and 26% in group B took>12 hours.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations